Creativity and the family tree: Human capital endowments and the propensity of entrepreneurs to patent - Albert N. Link; Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2011)
In this paper we show that the patenting behavior of creative entrepreneurs is correlated with the patenting behavior of their fathers, which we refer to as a source of the entrepreneurs' human capital endowments. Our argument for this relationship follows from established theories of developmental creativity, and our empirical analysis is based on survey data collected from MIT's Technology Review winners.
urn:nbn:de:101:1-20111011227
Keywords: J24; O31; 330; patents; entrepreneurship; human capital endowments; Humankapital; Persönlichkeitspsychologie; Patent; Generationenbeziehungen; Väter; USA